2008
DOI: 10.1007/s11064-007-9584-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ionized Calcium-binding Adapter Molecule 1 Immunoreactivity of the Hippocampal Dentate Gyrus and CA1 Region in Adult and Aged Dogs

Abstract: Similarities between age-related changes in the canine and human brain have resulted in the general acceptance of the canine brain as a model of human brain aging. The hippocampus is essentially required for intact cognitive ability and appears to be particularly vulnerable to the aging process. We observed changes in ionized calcium-binding adapter molecule 1 (Iba-1, a microglial marker) immunoreactivity and protein levels in the hippocampal dentate gyrus and CA1 region of adult (2-3 years) and aged (10-12 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…In addition, IFN-c protein levels were significantly increased in the spinal cord in the aged dogs compared to those in the adult dogs. This result is supported by previous studies that the expression of IFN-c was increased in the frontal portion of the SAMP10 brain [29] and increased in the dentate gyrus of aged dogs [25]. It has been reported that low concentrations of IFN-c modulate the adaptive immune response by directing microglia to differentiate to antigen presenting cells [30].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, IFN-c protein levels were significantly increased in the spinal cord in the aged dogs compared to those in the adult dogs. This result is supported by previous studies that the expression of IFN-c was increased in the frontal portion of the SAMP10 brain [29] and increased in the dentate gyrus of aged dogs [25]. It has been reported that low concentrations of IFN-c modulate the adaptive immune response by directing microglia to differentiate to antigen presenting cells [30].…”
Section: Discussionsupporting
confidence: 86%
“…In addition, Iba-1 protein levels were increased in the aged group. Indeed, many studies of age-related cellular, especially microglial, changes in the CNS have been performed [24][25][26][27]. Among the microglia classifications, ramified microglia are known as resting microglia.…”
Section: Discussionmentioning
confidence: 99%
“…These neuroinflammatory processes are normally transient, with microglia returning to a resting state as the immune stimulus is resolved. Microglia from the brain of aged gerbils (Choi et al 2007)and dogs (Hwang et al 2008) show a shift towards a more activated morphology (thickened and deramified processes) compared to young adults as determined by Iba1 staining. These morphological changes correspond with an increase in the expression of inflammatory markers in the brain of normal aged rats (Perry et al 1993), primates (Sheffield and Berman 1998), and humans (Streit and Sparks 1997;Kaunzner et al 2010).…”
Section: Age-related Changes In the Cns Immune Systemmentioning
confidence: 99%
“…Therefore, immune reaction assessment is crucial for effective treatment for SCI. Typically, IBA‐1 cells have prominent and ramified processes, indicating that some of them are microglia derived 29, 30. To investigate the inflammatory response, IBA‐1 immunohistochemistry was carried out following NF‐GS graft.…”
Section: Discussionmentioning
confidence: 99%